A Rapid and Simple Method for Lithium Purification and Isotopic Analysis of Geological Reference Materials by MC-ICP-MS - Zhu, Guanhong; Ma, Jinlong; Wei, Gangjian; Zhang, Le (Frontiers in Chemistry, 2020)
A simple method has been developed to purify lithium (Li) from matrix elements in geological reference materials, using a single-column packed with AGMP-50 cation exchange resin, followed by high-precision Li isotope measurements by multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS). A series of tests, such as different types of resin, loading amount of Li, loading volumes and various eluents, were conducted to ascertain the optimal conditions for Li purification and the effects of intensity, acidity, and presence of potential matrix elements on Li isotope measurements were also evaluated. In our experiment, Al and high-field-strength elements (HFSEs), such as Ti, Zr, and Hf, were eluted by 0.2 mol L–1 HCl + 0.3 mol L–1 HF, and 0.73 mol L–1 HCl was used to separate Li from other matrix elements, such as Na. This method is suitable for processing large amount of Li (60 ng to 270 ng) and enabling a Li recovery of close to 100%, with effective removal of matrix elements such as Na and Ca. Besides, our method achieves low matrix interferences (e.g., Na/Li << 1 and Ca/Li << 1 for rock and seawater via a single-column procedure; Ca/Li < 2 for carbonate via a two-column procedure) and also uses small volume of eluents and is rapid (~5 h), enabling a total separation to be completed in ~0.5 d. Using this method, we report Li isotopic compositions of various geological reference materials, including igneous rocks, seawater, and carbonate. The Li isotopic compositions are consistent with the data published previously for the analyzed reference materials. As such, the reported method is ideally suited for Li separation from multiple types of geological samples prior to isotopic analysis.